Rare bird documentation form for Northern Goshawk at Sandy Beach in Johnson County, 1982 - Staudt, Thomas J.et al (1982)
Rare bird documentation form for a Northern Goshawk at Sandy Beach in Johnson County, IA on December 18, 1982. Epson - sheet feed